Fundamentals of Structured Programming Using Fortran with SF/K and WATFIV-S - Holt R.C; Hume J.N.P (Reston Publishing Company, 1977)
This book is intended to form the basis of an introductory course in computing. Introduction to Programming, The Computer, SF/1: Programs that Calculate and Print, SF/2: Variables and Assignments, SF/3: Control Flow, Structuring Control Flow, SF/4: Alphabetic Information Handling, SF/5: Arrays, Structuring Your Attack on the Problem, SF/6: Controlling Input and Output, The Computer Can Read English, SF/7: Subprograms, Modular Programming, Searching and Sorting, SF/8: Files and Records, Data Structures, Scientific Calculations, Numerical Methods, Programming Language Compilers, Bibliography, Index.